Field propulsion system for space travel : physics of non-conventional propulsion methods for interstellar travel - Musha, Takaaki ([Bentham Books], 2011)
This e-book presents an overview of field propulsion systems for the use of space travel and interstellar travel. Such systems include warp drive and antigravity schemes, and rely on momentum transfer from the spacecraft to the external force field and from there to other masses in the cosmos in order to satisfy conservation of momentum. This cannot be achieved by the conventional methods like chemical propulsion and electric propulsion. The e-book should be a valuable source of information for researchers interested in spaceflight and propulsion physics.